Integrated biomimetic biphasic structures for high-strain-rate resistance and thermal insulation: Design, fabrication and performance characterization - Lijia Guo; Zhichao Dong; Zihao Chen; Xiaoyu Wang; Weijie Li; Ying Li (Engineering Science and Technology, an International Journal)
Addressing the critical need for multifunctional protective structures in military vehicles, this paper proposes three novel biphasic structures integrating high-strain-rate resistance and thermal insulation. Natural organisms have evolved lightweight, strong, and durable structures through long-term evolutionary adaptation. Guided by the tenets of biomimicry, three high-strain-rate resistant structural frameworks are firstly proposed and fabricated using 3D printing technology. Biphasic structures are fabricated by infusing phenolic resin into three novel structural frameworks through solution impregnation and thermal curing, followed by room temperature drying. The high-strain-rate resistances of the three biphasic structures are analyzed and compared employing Split Hopkinson Pressure Bar (SHPB) experiments, with the deformation process recorded via a high-speed camera. Based on micro-computerized tomography (μ-CT) images, the structural characteristics and porosity of the three biphasic structures after SHPB experiment are acquired. The thermal insulation properties of the structures are characterized using hot plate test and butane torch test. The dynamic mechanical properties and heat transfer mechanisms of the three biphasic structures are further analyzed using finite element simulations. The results show that the three structures exhibit both high-strain-rate resistance and thermal insulation properties, with the G-TPMS biphasic structure having the superior overall performance.